A blockchain-based system to enhance aircraft parts traceability and trackability for inventory management. (1st October 2021) - Ho, G.T.S.; Tang, Yuk Ming; Tsang, Kun Yat; Tang, Valerie; Chau, Ka Yin
Highlights: A blockchain-based system for Aircraft spare parts inventory management (ASPM). It enables accurate recording of spare parts' traceability data and tracking. The system was developed and validated using Hyperledger Fabric and Composer. It enhanced traceability of spare parts and information integrity in transactions. Sensitive analysis showed good performance in historical tracking and monitoring. Abstract: Aircraft spare parts inventory management (ASPM) has played a critical role in tracing and tracking spare parts as any related maintenance or movement shall be recorded. Traceability and trackability of data ensure the compliance of airworthiness requirements. The International Air Transport Association (IATA) has strongly emphasised the significance of quality traceability data throughout the aircraft part's life cycle, leading to enhanced inventory control accuracy, reduced maintenance error, and effective decision-making processes. However, with the rapid increase of spare parts types, the complexity of aircraft parts multi-stage supply chains leads to inefficient tracing and tracking operations with unsatisfactory traceability data quality and information security. This paper proposed a blockchain-based system that provided a managerial platform for accurate recording of spare parts traceability data with organisational consensus and validation using Hyperledger Fabric and Hyperledger Composer. A data model has been determined based on the existing ASPM, enabling information integrity during transaction operations. The channel mechanism has yielded a trustful data sharing platform between each contracting organisation for logistics and operational arrangements, which has enhanced information visibility and security. The blockchain-based system, executed under a decentralised ledger mechanism, shall improve the quality of traceability data and reliable information sharing within the spare parts supply chain. The enhanced blockchain-based inventory management system can establish the digital twin of aviation as part of Industry 4.0 in the future.